PENGENALAN KONFIGURASI PERANGKAT CISCO MENGGUNAKAN APLIKASI CISCO PACKET TRACER - Hendri Khusuma; Fajri M.Firdaus; Angga Esa Maulana; Rayhan R Fachrezi; Muhammad Zulfiqri; Kemal Luri Idris; Danu Wijaya; Dandi Saputra; Wiwin Winarti (Journal of Research and Publication Innovation, 2025)
The limited availability of computer network practice facilities in vocational schools, especially in rural areas such as SMKN 1 Sobang, poses a significant obstacle to improving students’ competencies in the field of Computer and Network Engineering (TKJ). To address this issue, a Community Service (PKM) activity was carried out by students of Pamulang University through training on the use of the Cisco Packet Tracer network simulation application. This activity aims to enhance students’ understanding of basic network concepts as well as their skills in configuring network devices virtually. The implementation method used a participatory educational approach, involving students in hands-on practice sessions and interactive discussions. The results of the activity showed a significant increase in students’ practical skills, active participation in learning, and the efficiency of the learning process without relying on expensive network hardware. Moreover, accompanying teachers gained new insights into simulation-based learning media that can be integrated into teaching and learning activities. This training also produced a teaching module as an output that can be used sustainably. Thus, the use of Cisco Packet Tracer has proven to be an effective and relevant solution for delivering practical and affordable computer network learning in vocational schools with limited facilities.